In-utero transfer, survival-focused care and survival to 28-days at 22-24 weeks’ gestation pre- and post- implementation of an extreme prematurity management guideline in Victoria, Australia - Jeanie LY Cheong; Alexis Shub; Calum T Roberts; Rosemarie A Boland; Michael J Stewart; Hannah G Gordon; Stefan C Kane; James Holberton (BMJ Paediatrics Open)
Background Care for infants born at 22–24 weeks’ gestation varies globally, with an increasing willingness to provide survival-focused (‘active’) care for infants born at 22 weeks’ gestation in recent years. This study aims to report changes in care for infants born at 22–24 weeks before and after the introduction of a statewide guideline for extreme prematurity (EP).Methods A retrospective cohort study was conducted, including all live births at 22–24 weeks in tertiary perinatal centres from 1 January 2015 to 31 December 2022 in Victoria, Australia. Medical records were reviewed to obtain antenatal history and perinatal outcomes. Data on in utero referral and transfer to tertiary perinatal centres were sourced from the statewide perinatal emergency retrieval service (Paediatric Infant Perinatal Emergency Retrieval, PIPER) database. Changes in PIPER referrals and transfers, survival-focused care and survival at 28 days preguideline and postguideline were assessed using logistic regression.Results Following the guideline, at 22 weeks’ gestation, there was an increase in referrals to PIPER and a 3.31 (95% CI 1.84 to 5.95) higher likelihood of in utero transfer to tertiary centres.Following the guideline, infants had a 6.67 (95% CI 1.40 to 31.72) higher likelihood of receiving survival-focused care at 22 weeks, and a 5.57 (95% CI 1.22 to 25.44) higher likelihood at 23 weeks. All 24-week live births received survival-focused care at birth. The 28-day survival for infants who received survival-focused care was unchanged preguideline and postguideline.Conclusion Following the publication of the EP guideline in Victoria, in utero referrals and transfers at 22 weeks’ gestation have increased, as has survival-focused management of inborn live births at 22–24 weeks.